2023
DOI: 10.3390/toxics11040362
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Biofortification Enhanced Grain Yield and Alleviated the Risk of Arsenic and Cadmium Toxicity in Rice for Human Consumption

Abstract: Arsenic (As) and Cadmium (Cd) are toxic to rice plants. However, selenium (Se) has the potential to regulate As and Cd toxicity. The present study aimed to evaluate the co-exposure to As5+ and Se6+ species in two rice cultivars, BRS Pampa and EPAGRI 108. The plants were divided into six groups and cultivated until complete maturation of the grains, under greenhouse conditions. Regarding total As and inorganic As (i-As) accumulation in grains, the highest concentrations were found for BRS Pampa. For Se, EPAGRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…By antagonizing the toxic effects of As, Se treatments have shown a mitigation effect on plant height, leaf dry weight, and grain yield [13]. Some exposure assessments revealed that Se biofortification could alleviate the As accumulation in rice [14] and significantly mitigate the harmful effect of As on the reduced yield of rice grain [15]. However, a study found that Se fertilizer treatment increased Se concentrations greatly but had no obvious effects on the concentrations of Cd and As in brown and milled rice [16].…”
Section: Introductionmentioning
confidence: 99%
“…By antagonizing the toxic effects of As, Se treatments have shown a mitigation effect on plant height, leaf dry weight, and grain yield [13]. Some exposure assessments revealed that Se biofortification could alleviate the As accumulation in rice [14] and significantly mitigate the harmful effect of As on the reduced yield of rice grain [15]. However, a study found that Se fertilizer treatment increased Se concentrations greatly but had no obvious effects on the concentrations of Cd and As in brown and milled rice [16].…”
Section: Introductionmentioning
confidence: 99%